R-optimal designs for second-order Scheffé model with qualitative factors - Ling LingChongqi Zhang; Guanghui Li; Xiaoyuan Zhu; Chongqi Zhang (AIMS Mathematics, 2022)
Considering a mixture model with qualitative factors, the R-optimal design problem is investigated when the levels of the qualitative factor interact with the mixture factors. In this paper, the conditions for R-optimality of designs with mixture and qualitative factors are presented. General analytical expressions are also derived for the decision function under the R-optimal designs, in order to verify that the resulting designs satisfy the general equivalence theorem. In addition, the relative efficiency of the R-optimal design is discussed.